The emperor's new road: China and the project of the century - Hillman, Jonathan E. (New Haven, USA: Yale University Press, Washington, USA: Center for Strategic and International Studies, 2020)
"China's Belt and Road Initiative is the world's most ambitious and misunderstood geoeconomic vision. To carry out President Xi Jinping's flagship foreign-policy effort, China promises to spend over one trillion dollars for new ports, railways, fiber-optic cables, power plants, and other connections. The plan touches more than one hundred and thirty countries and has expanded into the Arctic, cyberspace, and even outer space. Beijing says that it is promoting global development, but Washington warns that it is charting a path to global dominance. Taking readers on a journey to China's projects in Asia, Europe, and Africa, Jonathan E. Hillman reveals how this grand vision is unfolding. As China pushes beyond its borders and deep into dangerous territory, it is repeating the mistakes of the great powers that came before it, Hillman argues. If China succeeds, it will remake the world and place itself at the center of everything. But Xi may be overreaching: all roads do not yet lead to Beijing" --
Empire strikes back -- Project of the century -- Imperial echoes: technology and the struggle for control -- To Europe -- The crossroads: Central Asia -- The gatekeepers: Russia -- The bridgehead: Central and Eastern Europe -- To the sea The weak are powerful: Souteast Asia -- The black hole: Pakistan -- Game of loans: Sri Lanka -- Danger ahead -- Ware and PEACE: East Africa -- Refining the Blueprint.
Includes bibliographical references (pages 215-273) and index.
Keywords: Yi dai yi lu (Initiative : China); International economic relations; China -- Foreign economic relations; China